The Implementation of Literature in Class: The Reality of Implementing Literature Works in Senior High School - Shofia Kamal; Wahyu Indah Mala Rohmana; Arining Wibowo (ELITE Association Indonesia, 2023)
ABSTRACT The cruciality of literary work implementation in language learning class is settled, so it is included in the senior high school curriculum as a mandatory lesson. It is essential, for many advantageous aspects in EFL classroom can be obtained from implementing it. This study aimed to know the effectiveness of using literature as material for senior high school students in learning English. The data from this study was collected from interviews and literature reviews in the form of qualitative descriptive research. Some points discussed in the interview are used as primary data. Those included the implementation of literature in senior high school in Indonesia in general and the aim of implementing it, ways to apply narrative in EFL class, the advantages aspects of using drama as literary work to teach EFL class, challenges and solutions of implementing it, the reasons why it is applied in certain levels of education in Indonesia, and literature work implementation in Indonesia's curriculum. The research showed how literary work is worth to be applied in senior high school English courses. In sum, implementing literature in the EFL teaching and learning process was beneficial and prime. Keywords: Literary works; literature works; Senior High School; EFL